2018
DOI: 10.1111/acel.12753
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of m6A RNA modifications identified an age‐associated regulation of AGO2 mRNA stability

Abstract: SummaryGene expression is dynamically regulated in a variety of mammalian physiologies. During mammalian aging, there are changes that occur in protein expression that are highly controlled by the regulatory steps in transcription, post‐transcription, and post‐translation. Although there are global profiles of human transcripts during the aging processes available, the mechanism(s) by which transcripts are differentially expressed between young and old cohorts remains unclear. Here, we report on N6‐methyladeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(153 citation statements)
references
References 38 publications
3
143
0
Order By: Relevance
“…In addition to changes in DNA and histone methylation, certain mRNAs are less m6A methylated in old versus young human blood cells 72 . Thus, biological methylations exist in flux, responding to various pathologies and natural processes such as ageing.…”
Section: [H1] Methylation In Ageing and Cancermentioning
confidence: 99%
“…In addition to changes in DNA and histone methylation, certain mRNAs are less m6A methylated in old versus young human blood cells 72 . Thus, biological methylations exist in flux, responding to various pathologies and natural processes such as ageing.…”
Section: [H1] Methylation In Ageing and Cancermentioning
confidence: 99%
“…Specifically, downregulation of METTL14 in hepatocellular carcinoma (HCC) is associated with reduced miR-126a levels and increased metastatic capacity [31]. Furthermore, the METTL3-miR-25-3p-PHLPP2-AKT pathway is associated with pancreatic transformation [32], and m 6 A modifications of AGO2 mRNA contribute to cellular ageing by regulating global miRNA synthesis [33]. It has also been reported that YTHDC1 recognizes m 6 A marks in mESCs and is essential for X-inactive specific transcript (XIST) activity [34].…”
Section: The Biological Functions Of Rna M 6 a Modificationsmentioning
confidence: 99%
“…Emergent evidence has shown that the m6A modi cation plays an important role in the occurrence and development of human diseases. m6A levels in mRNA are found to be dynamic, varying during development, aging and in response to cellular stresses [9][10], indicating the role of m6A in age-related degeneration. Fat volume and obesity related (FTO) protein was the rst m6A demethylase [11].…”
Section: Introductionmentioning
confidence: 99%